(untitled) (Cadernos de Ética e Filosofia Política, 2020)
There are two ways to understand the agreement between men which culminates in the constitution of the multitude: the one of reason and the one of affections. In this article our purpose is to highlight the role of affections (in particular the sad ones) in the multitude’s constitution. To this end, we are going to start the discussion from Antonio Negri’s interpretation of Spinoza’s political work, which enphasizes mainly the role of joyful passions in the creation of a common ground and indicates a predominant tendency towards democracy in Spinoza’s project.